2020
DOI: 10.26877/eternal.v11i2.7563
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing English Discourse Markers in Efl Students’ Writing Production

Abstract: Fraser (1988; 1996; 1999) which are classified EDMs functions as ‘contrastive, ‘elaborative, and ‘inferential. This study designated the use of English discourse markers by University EFL students in writing production. To answer the research question on how do they disclose EDMs in producing writing, the writers employed a qualitative research approach. The object was the documentation of students’ writing result mediated on the writing class. The participants were 38 students of semester III in the academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Sharndama (2013), Andayani (2014), Purwadina and Huda (2014), Rahayu (2015), Faghih and Mousaee (2015), Ali and Mahadin (2016), Adewibowo, Imranuddin, & Azwandi (2018), Surjowati (2018), Rahayati, Herlina, & Surahmat (2021, and Raputri, Pratama, & Hartono (2022) reported that the use of elaborative markers being the most frequent discourse markers used. Conversely, Al Owayid (2018) and Sumardiyani and Susanto (2020) declared that contrastive discourse is the most frequently used by students in their writing. To sum up, the frequency of discourse markers used in writing varies based on the function of discourse markers and the kind of writing.…”
Section: Introductionmentioning
confidence: 99%
“…Sharndama (2013), Andayani (2014), Purwadina and Huda (2014), Rahayu (2015), Faghih and Mousaee (2015), Ali and Mahadin (2016), Adewibowo, Imranuddin, & Azwandi (2018), Surjowati (2018), Rahayati, Herlina, & Surahmat (2021, and Raputri, Pratama, & Hartono (2022) reported that the use of elaborative markers being the most frequent discourse markers used. Conversely, Al Owayid (2018) and Sumardiyani and Susanto (2020) declared that contrastive discourse is the most frequently used by students in their writing. To sum up, the frequency of discourse markers used in writing varies based on the function of discourse markers and the kind of writing.…”
Section: Introductionmentioning
confidence: 99%